(-2x+4)-(-6x-7)=

Simple and best practice solution for (-2x+4)-(-6x-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-2x+4)-(-6x-7)= equation:


Simplifying
(-2x + 4) + -1(-6x + -7) = 0

Reorder the terms:
(4 + -2x) + -1(-6x + -7) = 0

Remove parenthesis around (4 + -2x)
4 + -2x + -1(-6x + -7) = 0

Reorder the terms:
4 + -2x + -1(-7 + -6x) = 0
4 + -2x + (-7 * -1 + -6x * -1) = 0
4 + -2x + (7 + 6x) = 0

Reorder the terms:
4 + 7 + -2x + 6x = 0

Combine like terms: 4 + 7 = 11
11 + -2x + 6x = 0

Combine like terms: -2x + 6x = 4x
11 + 4x = 0

Solving
11 + 4x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + 4x = 0 + -11

Combine like terms: 11 + -11 = 0
0 + 4x = 0 + -11
4x = 0 + -11

Combine like terms: 0 + -11 = -11
4x = -11

Divide each side by '4'.
x = -2.75

Simplifying
x = -2.75

See similar equations:

| 3x-45=2y | | -6(2x-1)=0 | | x^2-15=-7x+2 | | 23-5n=-7(n-3)-4 | | 0.1x+0.2y=-0.2 | | Log^4*16=2 | | 7x-(5x+4)=9x-25 | | 25=2u+3u | | 2(x+4)4=0 | | 7.4x-13.4=31 | | 8u-u=21 | | 128-4y+2y=100 | | (c-3)(2c)=2c(c-3)-c^2+4 | | 16x-14=-110 | | 18x+14=13x+4 | | 5x+40=15-50 | | x+11=7x+65 | | 3a-3+2a=200-3a+2a | | (2b-4)=7b+2 | | 5=4x(1+x) | | 7.35x+66.15=132.3 | | -x+1=28+2x | | 3-4x+8x-5x=3x+12-15x+7 | | 4x-8.6=48.1-5x | | 8+12+(-9)-(-6)= | | 4x-7=29-2x | | 56-7x=-48+6x | | 5(x+1)=6-2(5x-7) | | x^2+9x-12=6+2x | | 8n+3=9 | | 18=13x+4x | | 0.6(w-12)=0.2w |

Equations solver categories